Efektivitas Komunikasi Reje dalam Melestarikan Tradisi Gotong Royong di Kampung Kung Kecamatan Pegasing - Viana Safrida Harahap; Suknah Suknah; Subhan AB (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The aim of this research is to determine reje communication strategies in preserving the tradition of mutual cooperation in Kung Village, Pegasing District. This research method uses qualitative methods with data collection techniques, namely observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and verification. The results of the research show that the effectiveness of communication is a means of taking steps to achieve a goal. Together with the effectiveness of communication, Reje Kampung Kung increases awareness of community mutual cooperation by taking an informative approach to the community and providing persuasive understanding personally and in groups. Realizing effectiveness is not always easy, there are many obstacles faced by Reje Kampung Kung in increasing awareness of mutual cooperation, namely the lack of basic understanding of the importance of preserving mutual cooperation. The obstacle faced by Reje Kampung Kung is the first, the busyness of each Kung village community, The next step is the emergence of a feeling of laziness, lack of socialization and social resonance which diminishes the spirit of mutual cooperation and becomes a selfish society.